Еврейские национальные колхозы Фрайдорфского и Лариндорфского районов Крымской АССР (20-30-е годы ХХ века) - Кондратюк, Г.Н. (Культура народов Причерноморья, 2013)
Важным компонентом национальной политики межвоенного периода стало переселение в
северные регионы Крымской АССР евреев из центральных областей страны. Программа аграризации
евреев должна была решить сложные социально-экономические проблемы штетлов. В Крыму были
выделены значительные массивы земли, под переселенческие программы, принявшие плановый характер.
С ростом количества еврейских крестьян создавались национальные сельские советы, школы, клубы и
избы-читальни. В процессе районирования в Крыму в 1930 и 1935 годах были созданы еврейские
национальные Фрайдорфский и Лариндорфский районы. Процесс переселения предполагал акцент на
коллективных формах обработки земли. Коллективные хозяйства стали доминирующей формой
организации еврейских крестьян. Важливою складовою національної політики міжвоєнного періоду стало переселення в
північні регіони Кримської АРСР євреїв з центральних областей Радянського Союзу. Програма
аграризації євреїв повинна була вирішити складні соціально-економічні питання єврейських містечок. В
Криму були виділені значні масиви землі для планового переселення євреїв. В Кримській АРСР були
створені національні єврейські сільради, школи, клуби та хати-читальні. В ході адміністративної
реформи було створено Фрайдорфський та Лариндорфській єврейські національні райони. Євреями-переселенцями створювались колективні форми обробки землі, які стали домінуючими. The migration of Jews from Central regions of the country to the Northern regions of the Crimean
ASSR was an important component of the national policy in the interwar period. The migration of Jews solved
socio-economic problems. Large tracts of land were allocated under the migration program in Crimea. National
Jewish regions with national village councils, schools, clubs, libraries were created in 1930 and 1935 years.
Collective farms have become the dominant form of organization of Jewish peasants.
The national policy concerning Jews in the 1920-1930th years was analyzed in this
article. Establishment of Jewish agricultural colonies in the peninsula was studied
The thesis is dedicated to integrated research of history of korenisation in Crimean ASSR in the period between
two world wars
The article deals with the analisis of the relations between the church and the state. The main components of
state and anti-religions politics were revealed. The correlation of national politics and anti-religions state
activity was observed. Specific character of anti-religions politics of the Crimean ASSR and its correlation with
the national indigenous politics was studied.
National policy in industry in Crimean ASSR in 1920-1930s in analyzed in the article. A campaign with the
establishment of national proletariat is characterized. Differentiation of korenizatsiya in industry in new
economic policy and industrialization is analyzed.